1998
DOI: 10.1243/0957650981536844
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the steady and non-steady flow performance of a highly loaded mixed flow turbine

Abstract: This paper describes a method for predicting the performance under both turbine inlet steady state and non-steady state flow conditions of a mixed flow turbine used for turbocharged internal combustion engines. The mixed flow turbine steady state performances computed with the steady state performance prediction method are in good agreement with the experimental results obtained in the Imperial College turbocompressor cold air test rig. The unsteady state performance is computed using a one-dimensional model b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 3 publications
1
18
0
Order By: Relevance
“…The impacts on different kinds of single stage turbine including double-entry turbine [4], waste-gated turbine [5,6], nozzled turbine [7] and variable geometry turbine [8] were studied. The characteristics of radial and mixed-flow turbines under pulsating flow conditions were disclosed in the investigations of Baines [9,10]. Under pulsating flow condition, the curve of mass flow rate versus expansion ratio is a hysteresis loop, which moves around the steady state performance curve.…”
Section: Introductionmentioning
confidence: 99%
“…The impacts on different kinds of single stage turbine including double-entry turbine [4], waste-gated turbine [5,6], nozzled turbine [7] and variable geometry turbine [8] were studied. The characteristics of radial and mixed-flow turbines under pulsating flow conditions were disclosed in the investigations of Baines [9,10]. Under pulsating flow condition, the curve of mass flow rate versus expansion ratio is a hysteresis loop, which moves around the steady state performance curve.…”
Section: Introductionmentioning
confidence: 99%
“…3 against a steady flow characteristic, deviation of the orbit from the characteristic line indicates that the QSF assumption tends to break down under certain pulse conditions. 7,8,17,21,22,26,27,28,29 Reduced…”
Section: The Quasi-steadiness Assumption and Other Modeling Apprmentioning
confidence: 99%
“…15,40,41 Some researchers indicated that pulse frequency was not as important as pulse amplitude in the performance of the system. 17,23,42 A recent simulation showed that for fixed amplitude of mass flow variation over a pulse, increasing pulse frequency increased the range of incidence, increasing the unsteadiness, thus lowering the efficiency. 21 Given the qualitative trends of increasing orbit variation with increases in frequency for fixed amplitude of oscillations 17,28 , frequency is seen to enhance unsteadiness, which leads to higher off-design losses and contradicts the claim for increased efficiency.…”
Section: Parametric Variations In Pulsed Flow Turbinesmentioning
confidence: 99%
“…This length selection was done supposing that half the mass flow enters the rotor at this point. This method is further refined and used in other works, such as in the work by Abidat et al [7] and by Costall et al [8]. The accuracy of this one-dimensional approach is limited for frequencies higher than 1000 Hz, and it is expected that a more realistic simulation of the volute, taking into account its lateral window flow, should provide better results.…”
Section: Introductionmentioning
confidence: 99%